Quality Imperative Value Addition and the Performance of Medium Scale Manufacturing Enterprises in Kenya - Mwasiaji, Evans (Journal of Accounting, Business and Finance Research, 2020)
Kenya’s manufacturing sector has stagnated at about USD 5 billion for over ten years in addition to lose of market share and competitiveness at the international level. This study therefore investigated quality imperatives and the performance of medium scale manufacturing enterprises in Kenya. Data was collected from 56 senior management staff from the sampled enterprises in Nairobi City County. Mean responses received in a Likert scale of 1 – 5 for each of the tested item was calculated by summing up all the codes and getting the average of the 56 respondents. These results revealed that there is a significant difference in the firms’ level of performance on various quality imperatives. To establish the level of performance of MSMEs in relation to the eighteen (18) tested items, a One-Way Analysis of Variance was conducted on the mean response on the items tested. The study established a mean response at 3.31 and a standard deviation at 0.80. The study concluded that Quality is critical in achieving sustainable competitive advantage. Hence the urgent need for MSMEs to further improve product quality and the production process for purposes of consumer and employee satisfaction and ultimately enhanced competitiveness at the local and international market. The study recommended that key processes within MSMEs should be reengineered to undertake the quality improvement journey, because their traditional management methods seem to be wholly inadequate to attain and sustain high quality in a globalized and competitive business environment.